Expanding current guidelines for management of COVID-19 focusing on low- and middle-income countries - Yudy Fonseca; Evangelina Urbina; Adnan Bhutta (AOSIS, 2022)
Within a short time, Coronavirus disease 2019 (COVID-19) has evolved into a pandemic spreading at a speed and scale that has been able to overwhelm even the most advanced healthcare systems quickly. Multiple guidelines published by organizations such as the WHO and US' CDC address the response to COVID-19 at the international, national, and local levels. Although these guidelines are meant to be globally accessible, implementing them is a challenge given the variability in the health care systems worldwide between low- and middle-income countries (LMIC) and high-income countries and even amongst different regions within each LMIC. We have chosen to evaluate the current guidelines focusing on LMIC and expand on the guidelines as necessary.